Composite silver-carbon material with three-dimensional conductive-lithium-conductive network, preparation method thereof, negative electrode and battery

CN122474616BActive Publication Date: 2026-10-23WEICHAI POWER CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202610967798.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-10-23
Estimated Expiration
2046-07-01

AI Technical Summary

Technical Problem

①结构稳定性差,体积膨胀缺乏缓冲,电极结构易破坏

Benefits of technology

1. 结构形态和界面稳定性:本发明的复合银碳材料,以气相银前驱体分子形式输运银源,气相的银前驱体可自由扩散至多孔碳纳米孔道内壁和外表面,通过饱和化学吸附实现银在孔道内壁、外表面原子级均匀沉积,银纳米颗粒被原位键合、限域锚定于多孔碳孔道内壁及外表面,实现分子级均匀复合,由于多孔碳基材内部的孔道结构是相互连通的,银纳米颗粒在孔道结构内壁及外表面沉积形成的银层也相互连通,形成一体化三维连通的银导-导锂电网络复合结构,而现有技术采用“颗粒间物理堆砌”,属于两相分离结构,因此,结构稳定性差,易脱离、团聚和相分离;本发明中的银纳米颗粒与多孔材料通过化学键键合,结合多孔碳孔的机械互锁构建了高强韧的银碳界面,二者之间紧密结合,大幅提升了电极在长循环过程中的结构完整性与机械接触稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122474616B_ABST
    Figure CN122474616B_ABST
Patent Text Reader

Abstract

The application belongs to the field of battery materials, and particularly relates to a composite silver-carbon material with a three-dimensional conductive-lithium-conductive network, a preparation method of the composite silver-carbon material, a negative electrode and a battery. The composite silver-carbon material comprises a porous carbon substrate, the porous carbon substrate has a crosslinked pore structure inside, and the inner wall and the outer surface of the pore structure have a silver nano layer; the silver nano layer forms a three-dimensional connected silver conductive-lithium-conductive network. In the application, the conductive-lithium-conductive network has high connectivity and stable mechanical structure, and the uniformity of silver and carbon distribution and the mechanical contact stability are greatly improved, so that the electrochemical performance is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery materials, and particularly relates to a composite silver-carbon material with a three-dimensional conductive-lithium-conducting network, its preparation method, negative electrode, and battery. Background Technology

[0002] All-solid-state lithium-ion batteries employing lithium metal anode systems exhibit significant energy density advantages. However, lithium metal anode systems face two major technical challenges in practical applications: firstly, lithium metal generates lithium dendrites during cycling; secondly, lithium dendrites induce coulombic efficiency decay. To address this bottleneck, related research proposes using Ag-C composite anode materials to replace pure lithium metal. Ag-C composite anode materials achieve controllability of the lithium deposition / stripping process through interface regulation mechanisms, significantly reducing lithium metal loss and contributing to excellent specific capacity and stable electrochemical cycling characteristics.

[0003] However, the current mainstream silver-carbon composite anode preparation process usually adopts slurry coating technology. This process has defects such as insufficient uniformity of material layer thickness and phase dispersion. These defects not only aggravate the growth of lithium dendrites, but also lead to increased interfacial impedance and rapid capacity decay. During long-term battery cycling, silver-carbon phase separation (silver migrating towards the anode current collector) is also very likely to occur, which poses a serious threat to the safety and long-term cycle stability of the battery.

[0004] Patent document CN120767292A discloses a preparation apparatus, method, silver-carbon anode sheet, and solid-state battery for a silver-carbon anode sheet. The preparation apparatus includes an unwinding device, a negative electrode slurry coating device, a spraying device, and a first drying oven. The unwinding device transports the negative electrode current collector to the negative electrode slurry coating device. The negative electrode slurry coating device coats both sides of the negative electrode current collector with a carbon-containing negative electrode slurry and dries it to obtain an intermediate electrode sheet. The spraying device sprays a silver-containing solution onto both sides of the intermediate electrode sheet to obtain a negative electrode roll. The first drying oven dries the negative electrode roll to obtain the silver-carbon anode sheet. This preparation apparatus has low energy consumption and cost, and high efficiency in preparing silver-carbon anode sheets.

[0005] Patent document CN120914202A discloses a silver-carbon anode sheet, which includes a negative electrode current collector and a negative electrode active coating attached to at least one surface of the negative electrode current collector; the negative electrode active coating includes silver particles and carbon particles; in a 100KX magnification scanning electron microscope image, the area of ​​the first particle with a particle diameter greater than or equal to 200 nm in the negative electrode active coating is S0, and the area of ​​the silver-carbon anode sheet in a 100KX magnification scanning electron microscope image is S, and S0 / S≤39.8%.

[0006] Patent document CN120073057A discloses a solid-state battery and its preparation method, comprising a positive electrode, a solid electrolyte layer, and a composite negative electrode stacked sequentially. The composite negative electrode includes a negative electrode and a Li3N-modified carbon source layer. The Li3N-modified carbon source layer is located between the negative electrode and the solid electrolyte layer. It constructs a functional layer that improves lithium-ion transport efficiency on the surface and inside the pores of the carbon material and serves as a modification layer between the solid electrolyte and the negative electrode interface, thereby enhancing the rapid transfer of lithium ions at the interface. The solid electrolyte is made into a uniform slurry and then directly coated onto the surface of the silver-carbon composite negative electrode sheet of the solid-state battery. Compared with the bonding and transfer method, this greatly enhances the interfacial contact between the negative electrode sheet and the electrolyte layer. This battery structure, in which the double-layer composite negative electrode integrates the electrolyte and is then bonded to the positive electrode, is conducive to improving the rapid transfer of lithium ions at the negative electrode interface and inside, promoting the uniform and rapid deposition of lithium on the current collector side, and thus improving the battery stability.

[0007] However, the existing methods described above mainly involve simply mixing silver particles with carbon particles (or modified carbon particles) or coating them separately to prepare silver-carbon composite anodes, which has the following drawbacks: ① Poor structural stability, lack of buffering for volume expansion, and easy damage to the electrode structure. During charging and discharging, as silver expands and contracts, it deposits on the current collector side, interrupting the electron transport path in the silver-carbon matrix and forming "dead silver" with extremely low utilization, resulting in rapid capacity decay. The silver particles and carbon particles have a "hard contact" with no buffer space. When silver expands after lithium insertion, it directly squeezes the surrounding carbon particles and may even crack the electrode plates; after delithiation and contraction, it leaves pores, and over time, the electrode structure gradually pulverizes and falls off.

[0008] ② Poor uniformity of microscopic distribution, with aggregation and phase separation occurring. Silver particles (especially nano-silver) have high surface energy and are prone to self-aggregation during mixing, forming local "silver islands." Meanwhile, carbon particle regions have insufficient silver content. This state of "macroscopic uniformity and microscopic heterogeneity" can lead to uneven electric field distribution inside the electrode, excessive local current density, accelerated lithium dendrite growth, and potential safety hazards.

[0009] ③ Poor controllability of the preparation process and low batch stability The effectiveness of mechanical mixing is highly dependent on equipment parameters (speed, time, medium, etc.), and it is difficult to avoid secondary oxidation of silver particles during the mixing process. Different batches of materials have large fluctuations in silver distribution, particle size, and purity, making it difficult to meet the consistency requirements of industrial mass production.

[0010] ④ The partial liquid-phase reduction deposition method relies on solution diffusion to bring the silver precursor into the porous carbon channels. However, due to the high surface tension of the solution and the "gas barrier" effect within the nanopores, it is difficult for the solution to truly penetrate into the micropores and deep channels. Even if it does penetrate, the reduction reaction often occurs preferentially at the pore opening, causing silver particles to accumulate at the pore opening and block the channels, while almost no silver is deposited in the depths of the channels. Summary of the Invention

[0011] To address the shortcomings of existing technologies, this invention provides a composite silver-carbon material with a three-dimensional conductive-lithium-conducting network, its preparation method, anode, and battery. By depositing silver in situ on the inner wall and outer surface of porous carbon, a highly interconnected and mechanically stable conductive-lithium-conducting network is constructed, significantly improving the uniformity of silver and carbon distribution and the stability of mechanical contact, thereby significantly enhancing electrochemical performance.

[0012] In a first aspect, the present invention provides a composite silver-carbon material having a three-dimensional conductive-lithium-conducting network. The composite silver-carbon material includes a porous carbon substrate, the inner wall of which has an interlinked pore structure, and the inner wall and outer surface of which have silver nanolayers; the silver nanolayers form a three-dimensional interconnected silver conductive-lithium-conducting network.

[0013] According to an embodiment of the present invention, the silver nanolayer is formed by silver nanoparticles, which are bonded to porous carbon.

[0014] According to an embodiment of the present invention, the silver nanoparticles are uniformly distributed on the inner wall and outer surface of the pore structure.

[0015] According to an embodiment of the present invention, the silver nanoparticles are uniformly distributed at the atomic level on the inner wall and outer surface of the pore structure.

[0016] According to an embodiment of the present invention, the thickness of the silver nanolayer is 1~500 nm, preferably 2~400 nm, and more preferably 5~300 nm.

[0017] According to an embodiment of the present invention, the silver loading in the composite silver-carbon material is 0.5% to 80%, preferably 1% to 70%, and more preferably 2% to 50%.

[0018] According to an embodiment of the present invention, the porous carbon substrate is selected from at least one of biomass-derived carbon, resin-based carbon, activated carbon, or other porous carbon materials with high porosity, such as activated carbon.

[0019] According to an embodiment of the present invention, the pore size of the porous carbon substrate is micropore or mesopore.

[0020] According to an embodiment of the present invention, the specific surface area of ​​the composite silver-carbon material is S1, and the specific surface area of ​​the corresponding porous carbon substrate is S2, where A = S1 / S2. %, 3%≤A≤15%, preferably 4%≤A≤10%, for example, A is 4%, 4.2%, 5%, 6%, 10%, 12%.

[0021] According to an embodiment of the present invention, the specific surface area of ​​the porous carbon substrate is 300~3000 m². 2 / g, preferably, the specific surface area of ​​the porous carbon substrate is 500~2000 m² / g. 2 / g, and more preferably, the specific surface area of ​​the porous carbon substrate is 800~1500 m² / g. 2 / g.

[0022] According to an embodiment of the present invention, the specific surface area of ​​the composite silver-carbon material is 10~500 m². 2 / g, preferably, the specific surface area of ​​the composite silver-carbon material is 30~300 m² / g. 2 / g, and more preferably, the specific surface area of ​​the composite silver-carbon material is 50~300 m² / g. 2 / g, for example, 50 m 2 / g、70 m 2 / g、90 m 2 / g、200 m 2 / g.

[0023] Secondly, the present invention provides a method for preparing the composite silver-carbon material as described above, comprising the following steps: Silver is deposited in situ on the inner and outer surfaces of a porous carbon substrate, forming a silver nanolayer on the inner and outer pores of the porous carbon.

[0024] According to embodiments of the present invention, the in-situ deposition includes liquid-phase in-situ reduction, photoinduced in-situ deposition, electrochemical in-situ deposition, and gas-phase in-situ deposition, with gas-phase in-situ deposition being preferred, for example, deposition using an atomic layer deposition reaction chamber (ALD reaction chamber).

[0025] According to an embodiment of the present invention, the preparation method includes the following steps: placing a porous carbon substrate in an ALD reaction chamber, first vaporizing a silver precursor and introducing it into the ALD reaction chamber, then introducing a reducing gas to react, and repeating the reaction several times to obtain the composite silver-carbon material.

[0026] According to an embodiment of the present invention, the silver precursor is Ag(fod)(PEt3).

[0027] According to an embodiment of the present invention, the vaporization temperature of the silver precursor is 70~200°C, preferably 120~150°C, for example 135°C.

[0028] According to an embodiment of the present invention, the reducing gas is selected from at least one of hydrogen, hydrogen plasma, formaldehyde, or hydrazine hydrate, for example, hydrogen plasma.

[0029] According to an embodiment of the present invention, the pulse time after the silver precursor vaporizes is 1-5s, for example, 2s.

[0030] According to an embodiment of the present invention, after the silver precursor is vaporized and introduced into the ALD reaction chamber, and before the reducing gas is introduced for reaction, a step of purging with an inert gas, such as nitrogen, is further included.

[0031] According to an embodiment of the present invention, the pulse duration of the reducing gas is 3 to 10 seconds, for example, 5 seconds.

[0032] According to an embodiment of the present invention, after the reaction is carried out with a reducing gas, the step of purging with an inert gas to remove reaction byproducts is further included.

[0033] Thirdly, the present invention provides a negative electrode material, the negative electrode material comprising the composite silver-carbon material as described above.

[0034] According to an embodiment of the present invention, the negative electrode material further includes an adhesive.

[0035] According to an embodiment of the present invention, the negative electrode material further includes a current collector.

[0036] According to an embodiment of the present invention, the composite silver-carbon material is mixed with a binder to form a negative electrode slurry, which is then coated onto the current collector to form a negative electrode material.

[0037] Fourthly, the present invention provides a battery comprising the composite silver-carbon material or the negative electrode material as described above.

[0038] Beneficial effects 1. Structural Morphology and Interface Stability: The composite silver-carbon material of this invention transports the silver source in the form of gaseous silver precursor molecules. The gaseous silver precursor can freely diffuse to the inner wall and outer surface of porous carbon nanopores. Through saturated chemical adsorption, silver is uniformly deposited at the atomic level on the inner wall and outer surface of the pores. The silver nanoparticles are in-situ bonded and confined and anchored to the inner wall and outer surface of the porous carbon pores, achieving molecular-level uniform composite. Since the pore structure inside the porous carbon substrate is interconnected, the silver layers formed by the silver nanoparticles deposited on the inner wall and outer surface of the pore structure are also interconnected, forming an integrated three-dimensional interconnected silver-conducting lithium battery network composite structure. In contrast, the existing technology uses "physical stacking between particles," which is a two-phase separation structure. Therefore, the structural stability is poor, and it is easy to detach, agglomerate, and separate into phases. In this invention, the silver nanoparticles and porous materials are chemically bonded, and the mechanical interlocking of the porous carbon pores constructs a high-strength and tough silver-carbon interface. The two are tightly bonded, which greatly improves the structural integrity and mechanical contact stability of the electrode during long-cycle processes.

[0039] 2. Electrochemical performance: Existing technologies struggle to achieve both uniform dispersion and volume expansion suppression at high silver content. This invention utilizes the self-limiting growth characteristics of ALD (Alternating Current Deposition). The self-limiting nature of the ALD reaction determines that only one atomic layer can be deposited per cycle. Therefore, the distribution of silver on the inner wall of the pores is atomically uniform, rather than the statistical distribution controlled by diffusion in liquid-phase methods. By precisely controlling the deposition thickness and distribution of silver, and relying on the pore confinement effect and buffer space of porous carbon, the volume expansion problem of silver is effectively alleviated. This achieves high capacity and excellent rate performance while obtaining an ultra-long cycle life, and the initial coulombic efficiency is significantly better than that of silver-carbon electrodes prepared by physical mixing.

[0040] 3. The composite silver-carbon material provided by this invention forms a three-dimensional interconnected silver-conducting and lithium-conducting network by constructing silver nanolayers on the inner and outer surfaces of a porous carbon substrate with cross-linked channels. During electrode operation, this silver network provides an efficient electron transport path. Simultaneously, the pore structure inside the porous carbon forms continuous lithium-ion diffusion channels after electrolyte wetting. Because the silver layer is extremely thin and uniform, it does not block the pore entrances, allowing lithium ions to migrate freely within the channels, effectively reducing lithium crystal formation. Therefore, the composite silver-carbon material possesses both excellent electronic conductivity and lithium-ion conductivity, achieving a dual-function integration of 'conductivity-lithium conduction'. Compared with conventional electrode materials, the material of this invention does not require the addition of additional conductive or lithium-conducting agents, yet exhibits significant advantages in battery rate performance, low-temperature performance, and cycle stability.

[0041] 4. The applicant unexpectedly discovered that, although the deposition of silver nanoparticles on porous carbon substrates, especially in the pores of the porous carbon substrates, significantly reduces the specific surface area of ​​the porous carbon substrates, the construction of a silver-carbon synergistic conductive-lithium-conducting network can effectively compensate for the insufficient electronic conductivity caused by high porosity, achieving synergistic optimization of electronic and ionic conductivity; the electrode prepared using the composite silver-carbon material of this invention has an efficiency greater than 99.2% at 0.5C, reaching a maximum of 99.8%; 300 th With a capacity retention rate greater than 98%, reaching up to 99.4%, and a battery short-circuit cycle count greater than 750, reaching up to 964, its electrical performance is far superior to that of silver-carbon materials obtained through "physical stacking between particles". Attached Figure Description

[0042] Figure 1 The diagram shows the structure of silver nanoparticles uniformly deposited on the surface and inside the pores of porous carbon. The left diagram shows the silver nanoparticles deposited on the outer surface of the porous carbon particles, and the right diagram shows the silver nanoparticles deposited in the pores inside the porous carbon. Detailed Implementation

[0043] The following detailed description, in conjunction with specific embodiments, provides a more comprehensive overview of the porous carbon-based composite silver-carbon anode with in-situ deposited silver, its preparation method, and its applications. It should be understood that the following embodiments are merely illustrative and explanatory of the invention and should not be construed as limiting the scope of protection of the invention. All technologies implemented based on the above-described content of this invention are covered within the scope of protection intended by this invention.

[0044] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.

[0045] Example 1: Porous carbon (specific surface area 2200 m²) 2 The porous carbon powder (with a pore size distribution dominated by micropores) was dried in a vacuum drying oven at 120℃ for 12 h to remove adsorbed moisture. 1.5 g of the dried porous carbon was taken and evenly spread on the sample tray of the ALD (Atomic Layer Deposition) reaction chamber, ensuring that the thickness of the porous carbon powder did not exceed 1.5 mm to facilitate precursor diffusion.

[0046] Ag(fod)(PEt3) (triethylphosphine (hexafluoroacetylacetone) silver), which is more suitable for deposition in three-dimensional structures, was selected as the silver precursor. It was heated to 135°C to vaporize and then introduced into the ALD reaction chamber. The pulse time for the silver precursor was set to 1.5 seconds, followed by nitrogen purging for 8 seconds. After the silver precursor gas entered the reaction chamber, it underwent chemical adsorption... (See...) Figure 1As shown, the silver precursor is attached to the inner and outer pore surfaces of the porous carbon powder (referring to the outer surface of the porous carbon powder and the inner surface of the pores); then, plasma-activated hydrogen is used as the reducing gas for the co-reaction. The pulse time of the hydrogen plasma is set to 4 seconds. After the hydrogen plasma reduces the adsorbed silver precursor to Ag, it is then purged with high-purity nitrogen for 12 seconds to remove the reaction byproducts. This process is repeated 200 times to obtain silver carbon.

[0047] BET testing showed that the specific surface area of ​​porous carbon after silver deposition decreased to 200 μm. 2 / g, proving the successful deposition of silver nanolayers inside and outside the pores. Assembly: The main material was prepared by mixing silver, carbon and PVDF (polyvinylidene fluoride) binder at a mass ratio of 95:5 to obtain a slurry, which was then coated onto the surface of copper foil (100-micron wet coating), dried and then assembled into a full cell.

[0048] Example 2: Porous carbon (specific surface area 1500 m²) 2 / g, with pore size distribution mainly mesoporous), dried in a vacuum drying oven at 120℃ for 12 h to remove adsorbed moisture, take 1.5 g of dried porous carbon, and spread it evenly on the sample tray of the ALD reaction chamber, ensuring that the powder layer thickness does not exceed 1.5 mm to facilitate precursor diffusion.

[0049] Ag(fod)(PEt3), which is more suitable for deposition in three-dimensional structures, was selected as the silver precursor. It was heated to 135°C to vaporize and sent into the ALD reaction chamber. The pulse time of the silver precursor was set to 2 seconds, and nitrogen was purged for 8 seconds. After the silver precursor gas entered the reaction chamber, it was attached to the inner and outer pore surfaces of the porous carbon powder through chemical adsorption. Then, plasma-activated hydrogen was used as the reducing gas for co-reaction. The pulse time of the hydrogen plasma was set to 5 seconds. After the hydrogen plasma reduced the adsorbed silver precursor to Ag, it was purged with high-purity nitrogen for 12 seconds to remove reaction byproducts. The cycle was repeated 300 times to obtain silver carbon.

[0050] BET testing showed that the specific surface area of ​​porous carbon after silver deposition decreased to 90 μm. 2 / g, proving the successful deposition of silver nanoparticles inside and outside the pores. The main material is prepared by mixing silver carbon and PVDF binder at a mass ratio of 95:5 and then coating it onto the surface of copper foil (100 micrometer wet coating). After drying, the full cell is assembled.

[0051] Example 3: Porous carbon (specific surface area 1500 m²) 2 / g, with pore size distribution mainly mesoporous), dried in a vacuum drying oven at 120℃ for 12 h to remove adsorbed moisture, take 1.5 g of dried porous carbon, spread it evenly on the sample tray of the ALD reaction chamber, and ensure that the powder layer thickness does not exceed 1.5 mm to facilitate precursor diffusion.

[0052] Ag(fod)(PEt3), which is more suitable for deposition in three-dimensional structures, was selected as the silver precursor. It was heated to 135°C to vaporize and sent into the ALD reaction chamber. The pulse time of the silver precursor was set to 3 seconds, and nitrogen was purged for 8 seconds. After the silver precursor gas entered the reaction chamber, it was attached to the inner and outer pore surfaces of the porous carbon powder through chemical adsorption. Then, plasma-activated hydrogen was used as the reducing gas for co-reaction. The pulse time of the hydrogen plasma was set to 7 seconds. After the hydrogen plasma reduced the adsorbed silver precursor to Ag, it was purged with high-purity nitrogen for 12 seconds to remove reaction byproducts. After 500 cycles, silver carbon was obtained.

[0053] BET testing showed that the specific surface area of ​​porous carbon after silver deposition decreased to 70 μm. 2 / g, demonstrating the successful deposition of silver nanolayers inside and outside the pores. Assembly: The main material was prepared by mixing silver, carbon, and PVDF binder at a mass ratio of 95:5 to obtain a slurry, which was then coated onto the surface of copper foil (100-micron wet coating). After drying, the full cell was assembled.

[0054] Example 4: Porous carbon (specific surface area 1100 m²) 2 / g (pore size distribution is mainly mesoporous and macroporous), dried in a vacuum drying oven at 120℃ for 12 h to remove adsorbed moisture. Take 1.5 g of dried porous carbon and spread it evenly on the sample tray of the ALD reaction chamber, ensuring that the powder layer thickness does not exceed 1.5 mm to facilitate precursor diffusion.

[0055] Ag(fod)(PEt3), which is more suitable for deposition in three-dimensional structures, was selected as the silver precursor. It was heated to 135°C to vaporize and sent into the ALD reaction chamber. The pulse time of the silver precursor was set to 3 seconds, and nitrogen was purged for 8 seconds. After the silver precursor gas entered the reaction chamber, it was attached to the inner and outer pore surfaces of the porous carbon powder through chemical adsorption. Then, plasma-activated hydrogen was used as the reducing gas for co-reaction. The pulse time of the hydrogen plasma was set to 7 seconds. After the hydrogen plasma reduced the adsorbed silver precursor to Ag, it was purged with high-purity nitrogen for 12 seconds to remove reaction byproducts. The cycle was repeated 1000 times to obtain silver carbon.

[0056] BET testing showed that the specific surface area of ​​porous carbon after silver deposition decreased to 50 μm. 2 / g, demonstrating the successful deposition of silver nanolayers inside and outside the pores. Assembly: The main material was prepared by mixing silver, carbon, and PVDF binder at a mass ratio of 95:5 to obtain a slurry, which was then coated onto the surface of copper foil (100-micron wet coating). After drying, the full cell was assembled.

[0057] Comparative Example 1: PVDF (polyvinylidene fluoride) powder was dried in an oven at 60°C for 4 h to remove surface adsorbed water; PVDF powder was accurately weighed and dissolved in NMP (N-methyl-2-pyrrolidone), and heated and stirred at 60°C for 2-3 h with a magnetic stirrer until completely dissolved to form a clear and transparent PVDF solution; silver powder and conductive carbon black were dry-mixed and pre-dispersed in a mortar or small mixer at a weight ratio of 1:3 for 5 min; the pre-mixed silver / carbon powder was added to the PVDF solution (at a mass ratio of 95 (silver carbon): 5 (binder)) and stirred and dispersed using a high-speed homogenizer for 30 min; during the stirring process, a small amount of NMP was added in 2-3 batches to adjust the viscosity of the slurry to meet the coating process requirements; the slurry was vacuum degassed for 15 min before coating to remove air bubbles mixed in during the stirring process, and the slurry was scraped onto the copper foil surface (100 micrometer wet coating), and then the full cell was assembled after drying.

[0058] Comparative Example 2: 0.75 g of carbon black was ultrasonically dispersed in 150 mL of deionized water and sonicated for 60 min to prepare a suspension with a concentration of 0.5-2 mg / mL. 0.394 g of AgNO3 solution was slowly added dropwise to the suspension, and the mixture was magnetically stirred at room temperature for 30-60 min to allow the AgNO3 to dissolve. + It is fully adsorbed onto the carbon surface. Take 0.176 g of NaBH4 and dissolve it in 20 mL of ice water (0-5℃). Stir gently until dissolved. NaBH4 reacts with water exothermically and decomposes; therefore, pre-cooled deionized water must be used, and the NaBH4 solution must be prepared in an ice bath. Adsorbed Ag + The carbon suspension was then transferred to an ice-water bath, maintaining the system temperature at 0-5°C. Vigorous magnetic stirring was initiated to obtain the reaction solution. Using a dropper or syringe, NaBH4 solution was slowly added dropwise to the reaction solution at a rate of approximately 1 drop / second. The solution gradually turned grayish-black and produced a large number of bubbles (H2). After the addition was complete, the reaction was continued in the ice-water bath for 30 minutes to ensure the Ag... + Complete reduction: Centrifuge the reaction solution, discard the supernatant, and wash the precipitate three times with deionized water and then twice with anhydrous ethanol to accelerate subsequent drying.

[0059] The washed precipitate was transferred to a petri dish and vacuum dried at 60-80℃ for 12 h to obtain Ag@C composite powder. The Ag@C composite powder was added to PVDF adhesive (at a ratio of 95 (silver-carbon):5 (PVDF binder)) and dispersed using a high-speed homogenizer for 30 min. During stirring, small amounts of NMP were added in 2-3 batches to adjust the slurry viscosity to meet coating process requirements. The slurry was vacuum degassed for 15 min before coating to remove air bubbles introduced during stirring. The slurry was then coated onto the copper foil surface (100-micron wet coating), dried, and the entire cell was assembled.

[0060] The batteries prepared in Examples 1-4 and Comparative Examples 1-2 were tested as follows: The assembled batteries were subjected to constant current charge-discharge tests in a 55°C constant temperature chamber using a charge-discharge instrument. The capacity retention rate was tested at 0.05C and 0.5C rates, and the number of cycles with short circuits (the number of cycles corresponding to efficiency below 98%, continuous overcharging, or sudden voltage drop) was recorded.

[0061] Table 1. Performance of batteries prepared in Examples 1-4 and Comparative Examples 1-2 As shown in Table 1, the silver-carbon assembled full cells prepared using the method of this invention have an efficiency greater than 99.2% at 0.05C, with a maximum efficiency of 99.8%; 300 th The capacity retention rate is greater than 98%, reaching a maximum of 99.4%, and the number of short circuit cycles is greater than 750, reaching a maximum of 964; far exceeding that of Comparative Example 1 and Comparative Example 2.

[0062] The specific embodiments of the present invention have been described above by way of example. However, the scope of protection of the present invention is not limited to the above exemplary embodiments. Any modifications, equivalent substitutions, improvements, etc., made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A composite silver-carbon material with a three-dimensional conductive-lithium-conductive network, characterized in that, The composite silver-carbon material comprises a porous carbon substrate, wherein the porous carbon substrate has a cross-linked pore structure inside, and the specific surface area of ​​the porous carbon substrate is 300~3000 m². 2 / g, the specific surface area of ​​the composite silver-carbon material is 10~500 m² / g. 2 / g, the inner wall and outer surface of the pore structure have silver nanolayers; the silver nanolayers on the inner wall and outer surface of the pore structure are interconnected to form an integrated three-dimensional interconnected silver conductive-lithium conductive network composite structure; The specific surface area of ​​the composite silver-carbon material is S1, and the corresponding specific surface area of ​​the porous carbon is S2, where A = S1 / S2*%, 3% ≤ A ≤ 15%; the pore size of the porous carbon substrate is micropore or mesopore, and the silver nanolayer is obtained by depositing silver in an atomic layer deposition reaction chamber on the porous carbon substrate.

2. The composite silver-carbon material with a three-dimensional conductive-lithium-conducting network according to claim 1, characterized in that, The silver nanolayer is formed by silver nanoparticles, which are bonded to porous carbon and are uniformly distributed on the inner wall and outer surface of the pore structure.

3. The composite silver-carbon material with a three-dimensional conductive-lithium-conducting network according to claim 1, characterized in that, The thickness of the silver nanolayer is 1~500 nm; the silver loading in the composite silver-carbon material is 10%~80%.

4. A method for preparing the composite silver-carbon material as described in any one of claims 1-3, characterized in that, Includes the following steps: A porous carbon substrate is placed in an ALD reaction chamber. The silver precursor is first vaporized and introduced into the ALD reaction chamber, and then a reducing gas is introduced to react. The reaction is repeated several times to obtain the composite silver-carbon material.

5. The method for preparing the composite silver-carbon material according to claim 4, characterized in that, The silver precursor is selected from Ag(fod)(PEt3).

6. A negative electrode material, said negative electrode material comprising the composite silver-carbon material as described in any one of claims 1-3 or the composite silver-carbon material prepared by the method described in any one of claims 4-5.

7. A battery comprising the composite silver-carbon material as described in any one of claims 1-3, the composite silver-carbon material prepared by the method described in any one of claims 4-5, or the negative electrode material as described in claim 6.

Citation Information

Patent Citations

  • Solid-state battery and preparation method thereof

    CN120073057A

  • Preparation equipment and method of silver-carbon negative electrode plate, silver-carbon negative electrode plate and solid-state battery

    CN120767292A

  • Preparation method of coating slurry, silver-carbon negative plate, preparation method of silver-carbon negative plate and solid-state battery

    CN120914202A

  • Method for preparing silver film by atomic layer deposition technology

    CN111254413A

  • Silicon-carbon negative electrode material, preparation method thereof and battery

    CN120895629A